Symbolism of cultural landscape in urban waterfront design of Pantai Lido, Johor Bahru, Malaysia - Hussain, Mohd Amirul (2021)
Pantai Lido of Johor Bahru has a diversity of cultures, beautiful landscapes, and unique nature along its waterfront. This diversity, at one time, has made Pantai Lido a tourist option for domestic as well as international visits. After more than fifty decades of being a landmark of magnificent landscape for Johor Bahru, Pantai Lido is now experiencing an alteration which has resulted in the de-territorialisation of its cultural landscape. This has inevitably eroded the identity and symbolism of the place. Thus, the main objective of this study is to explore and understand the symbolism of the cultural landscape in the waterfront design at Pantai Lido, as well as to preserve Pantai Lido from the deterritorialisation through four sub-objectives: 1) To discover the meaning of cultural landscape at Pantai Lido, 2) To explore the symbolism of cultural landscape at Pantai Lido, 3) To investigate the challenges that are faced in designing the cultural landscape at Pantai Lido, and 4) To determine the essential considerations that are needed to design an emblematic cultural landscape at Pantai Lido. To achieve the objectives of the study, the qualitative research method using a case study approach was conducted to explore the symbolism of the cultural landscape, where Pantai Lido was selected as the location for data collection. A total of 22 informants comprising16 local communities were involved in this study via in-depth semi-structured interviews and six local authorities participated in a focus group discussion (FGD). Accordingly, the primary data gathered from the in-depth, semi-structured interviews were thus supported by relevant information from the FGD. Additional data were derived from participant observations, document analysis, and audio-visual materials. This study has significantly contributed to the body of knowledge. It enhances the conceptual understanding in the use of cultural landscape characteristics as design strategies to develop cultural landscape symbolism at Pantai Lido’s urban waterfront. Consequently, the findings of this study can assist the state government and related parties in developing a cultural landscape design strategies framework for the urban waterfront at Pantai Lido, and thus mitigate the deterritorialisation of the cultural landscape at the said location. Thus, the contributions of this study are not only beneficial to assist in the planning of the cultural landscape at Pantai Lido, but can also be applied to other similar regions throughout Malaysia Moreover, the contribution of the design framework is not limited to only mitigating the de-territorialisation of the cultural landscape in Malaysia, but also for the management of sustaining the urban waterfront landscape.